2021
DOI: 10.1002/erv.2855
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions in binge spectrum eating disorders with comorbid compulsive buying

Abstract: Objective: The aims were to explore if bulimic spectrum disorders (BSD) patients, who also present comorbid compulsive buying (CB), could represent a specific subtype considering its neuropsychological performance; to present a descriptive analysis of different clinical features; and to explore how these variables could influence treatment outcome. It was hypothesised that the comorbid group will present worse neuropsychological performance that will lead to a worse treatment outcome. Method:The study has a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…In addition, BSD patients performed slightly worse than patients with GD, demonstrating a trend to more impulsive decision-making. Attending to earlier findings, it was expected that both clinical groups presented difficulties in decision-making [31, 32, 48, 77]. Evidence also indicates that GD and BSD patients share a preference for immediate rewards (i.e., binging or gambling) regardless of future consequences [78, 79].…”
Section: Discussionmentioning
confidence: 97%
“…In addition, BSD patients performed slightly worse than patients with GD, demonstrating a trend to more impulsive decision-making. Attending to earlier findings, it was expected that both clinical groups presented difficulties in decision-making [31, 32, 48, 77]. Evidence also indicates that GD and BSD patients share a preference for immediate rewards (i.e., binging or gambling) regardless of future consequences [78, 79].…”
Section: Discussionmentioning
confidence: 97%
“…Compulsive shopping has high rates of comorbidity with other disorders, including eating disorders [ 20 , 21 , 22 ].…”
Section: The Relationship Between Compulsive Buying and Eating Disord...mentioning
confidence: 99%
“…Several studies have reported that CB and EDs are highly comorbid. In this line, a study by Munguía et al (2021b) reported that the co-occurrence of CB and EDs leads to a more severe clinical profile and a worse treatment outcome when compared to healthy controls or patients without this comorbidity (de Mattos et al, 2018). In contrast, the prevalence of GD and EDs appears to be lower (Jiménez-Murcia et al, 2013).…”
Section: Introductionmentioning
confidence: 98%